Vadim Kuznetsov. Informal Biography by Eyes of His First Adviser - Komarov, I.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
The paper is dedicated to the memory of prominent theoretical physicist and mathematician Dr. Vadim Kuznetsov who worked, in particular, in the fields of the nonlinear dynamics, separation of variables, integrability theory, special functions. It includes his short research biography, an account of the start of his research career and the list of publications.